2017
DOI: 10.1002/cam4.1050
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 long isoform has opposite effects on the growth of human mastocytosis and medullary thyroid carcinoma cells

Abstract: Carcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) is expressed in a number of tumor cell types. The immunoreceptor tyrosine‐based inhibitory motif (ITIM)‐containing isoforms of this molecule which possess a long cytoplasmic tail (CEACAM1‐L) generally play inhibitory roles in cell function by interacting with Src homology 2 domain‐containing tyrosine phosphatase (SHP)‐1 and/or SHP‐2. Src family kinases (SFKs) are also known to bind to and phosphorylate CEACAM1‐L isoforms. Here, we report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Studies using mast cell-deficient mice, such as Kit W/Wv mice and Kit Wsh/Wsh mice, revealed that mast cells protect against parasitic infections including Strongyloides ratti and Strongyloides brasiliensis [7,8], as well as the venoms of honeybees or vipers [9]. Mast cells are (KIR) 2DL4 [19][20][21][22][23][24][25][26][27][28][29][30][31]. These include inhibitory receptors characterized by immunoreceptor tyrosine-based inhibitory motifs (ITIMs) within their cytosolic domains ( Figure 1) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several receptors have been reported to suppress mastocytosis growth . The effects are commonly mediated by phosphatases including Src homology domain 2‐containing protein tyrosine phosphatases (SHPs) and SH2 homology domain‐containing inositol 5′‐phosphatases (SHIPs).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested by Zhang et al that miR‐30d was degraded in human colon cancer cell lines in contrast to normal colon epithelial cell line . As for dysregulation of CEACAM1, a recent study has unveiled that CEACAM1 exerted a high expression in multiple myeloma, and Ueshima et al have provided evidence that expression of CEACAM1 was heightened in both neoplastic mast cells and medullary thyroid carcinoma cell lines …”
Section: Discussionmentioning
confidence: 99%